2019
DOI: 10.7554/elife.49818
|View full text |Cite
|
Sign up to set email alerts
|

VEGF/VEGFR2 signaling regulates hippocampal axon branching during development

Abstract: Axon branching is crucial for proper formation of neuronal networks. Although originally identified as an angiogenic factor, VEGF also signals directly to neurons to regulate their development and function. Here we show that VEGF and its receptor VEGFR2 (also known as KDR or FLK1) are expressed in mouse hippocampal neurons during development, with VEGFR2 locally expressed in the CA3 region. Activation of VEGF/VEGFR2 signaling in isolated hippocampal neurons results in increased axon branching. Remarkably, inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…VEGFR-2 mediates the main physiological functions of VEGF. VEGF, the vascular permeability factor (VPF), is an essential and crucial growth factor for vascular endothelial cells, and plays various roles in cardiovascular system ( Wang et al, 2019 ), central nervous system ( Bellon et al, 2010 ; Luck et al, 2019 ), hematopoiesis ( Hooper et al, 2009 ), development ( Karaman et al, 2018 ), and tumorigenesis ( Volz et al, 2020 ; Zhong et al, 2020 ). Despite having so many physiological functions, the main physiological functions of VEGF on endothelial cells are almost all achieved by activating VEGFR-2, including stimulating endothelial cell proliferation, increasing vascular permeability, and chemotaxis to endothelial cells, etc.…”
Section: Vegfr-2 Physiological Functions and Pathological Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGFR-2 mediates the main physiological functions of VEGF. VEGF, the vascular permeability factor (VPF), is an essential and crucial growth factor for vascular endothelial cells, and plays various roles in cardiovascular system ( Wang et al, 2019 ), central nervous system ( Bellon et al, 2010 ; Luck et al, 2019 ), hematopoiesis ( Hooper et al, 2009 ), development ( Karaman et al, 2018 ), and tumorigenesis ( Volz et al, 2020 ; Zhong et al, 2020 ). Despite having so many physiological functions, the main physiological functions of VEGF on endothelial cells are almost all achieved by activating VEGFR-2, including stimulating endothelial cell proliferation, increasing vascular permeability, and chemotaxis to endothelial cells, etc.…”
Section: Vegfr-2 Physiological Functions and Pathological Rolesmentioning
confidence: 99%
“…During embryonic development, the VEGFR-2 signaling pathway is involved in the proliferation, growth, and migration of hematopoietic and early endothelial cells (angioblasts) ( Dias et al, 2000 ; LeCouter et al, 2004 ). Several studies showed that the VEGF/VEGFR-2 signaling directly regulates the development and function of neurons, e.g., increased axon branching ( Luck et al, 2019 ).…”
Section: Vegfr-2 Physiological Functions and Pathological Rolesmentioning
confidence: 99%
“…In addition, external cues that induce collaterals from sensory stem axons in the spinal cord have not yet been characterized. However, a recent study characterized VEGF and its receptor VEGFR2 in the hippocampus as an axon branching system (Luck and others 2019). Based on the expression of the VEGF in the spinal cord and its receptor VEGFR2 in DRG neurons at early stages of development, it would be of interest to investigate collateral branching from sensory stem axons in the spinal cord (Himmels and others 2017).…”
Section: Npr2-mediated Cgmp Signaling Does Not Regulate Collateral (Imentioning
confidence: 99%
“…This study was novel in investigating the correlation between CBF based on 3D-ASL, VEGF expression, and cognition in a T2DM rat model. However, it had certain limitations: (1) Previous studies revealed that the effect of VEGF expression on memory was primarily a result of axonal loss, demyelination, or changing plasticity of mature neurons[ 12 , 39 , 47 ]. The possibility that the decreased VEGF level might cause DACD via hippocampal neural injury was not examined in the present study; and (2) Previous findings indicated that each division of the hippocampus had different functions[ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF; also known as VEGF-A) is involved in microvascular structure and function and the development of axon branching[ 11 , 12 ]. Many studies have shown that enhancing VEGF signaling or VEGF restoration can ameliorate cognitive function[ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%